Positive and Negative Aspects of Inclusion Services - Hayes, Christye (Journal of the American Academy of Special Education Professionals, 2014)
The purpose of this research paper was to investigate the conceptions and misconceptions of an inclusive education. Inclusion was formulated upon three core inclusionary principles, these being: setting diverse suitable learning challenges, responding to needs of pupils, and overcoming potential barriers to learning and assessment for individuals and groups of children. As a result of No Child Left Behind (NCLB) and the even more recent mandates of the revised Individual with Disabilities Act (IDEA) of 2004, which defines "highly qualified" in new ways, it has become increasingly important for schools to utilize their resources using more effective and creative means.